Molecular Monitoring of Flavivirus Infections (West Nile Virus and Dengue Virus) Among Culicidae Mosquitoes in Southern Iran - Masoumeh Amin; Hamideh Edalat; Hamidreza Basseri; Morteza Zaim; Kourosh Azizi; Mostafa Salehi- Vaziri; Sahar Khakifirouz; Mohsen Kalantari; Mozaffar Vahedi; Saideh Yousefi; Parisa Amin (Journal of Health Sciences and Surveillance System)
Background: Mosquitoes (Diptera: Culicidae) are significant vectors of mosquito-borne diseases prevalent across temperate and tropical regions. Understanding the abundance and distribution of these vectors is essential for studying the ecoepidemiology of mosquito-borne diseases.Methods: This cross-sectional study aimed to identify mosquito populations (Culicidae) and conduct molecular analysis for Flavivirus infections, explicitly focusing on West Nile Virus (WNV) and Dengue Virus (DENV) in Fars Province, Southern Iran. Mosquitoes were collected from 23 stations across urban and rural areas and migratory bird habitats in five counties, using hand catch with manual aspirators, CDC light traps with CO2, and human and animal bait methods from April to December 2018. Molecular screening for Flavivirus RNA, including WNV and DENV, was performed using a specific PCR technique.Results: 8212 adult mosquitoes were collected, representing four genera and nine species. The most prevalent species were Culex pipiens (54.20%), Culiseta longiareolata (30.40%), and Culex sinaiticus (10.25%). Molecular screening was conducted on the 8212 mosquitoes grouped into 150 pools based on sex, species, and trapping location. None of the pools tested were positive for Flavivirus RNA.Conclusion: This study highlights the importance of monitoring mosquito species distribution and emphasizes the need for enhanced Flavivirus surveillance and long-term monitoring programs in the region to understand the risk of disease transmission better.